2002
DOI: 10.1152/japplphysiol.00399.2001
|View full text |Cite
|
Sign up to set email alerts
|

Thermal regulation and comfort during a mild-cold exposure in young Japanese women complaining of unusual coldness

Abstract: We examined body core and skin temperatures and thermal comfort in young Japanese women suffering from unusual coldness (C, n = 6). They were selected by interview asking whether they often felt severe coldness even in an air-conditioned environment (20-26 degrees C) and compared with women not suffering from coldness (N, n = 6). Experiments were conducted twice for each subject: 120-min exposure at 23.5 degrees C or 29.5 degrees C after a 40-min baseline at 29.5 degrees C. Mean skin temperature decreased (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
111
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 26 publications
(34 reference statements)
5
111
2
Order By: Relevance
“…[23][24][25] It is well demonstrated that postmenopausal status is associated with significantly reduced arterial NO activity 24) and thus leads to an increase in local vascular resistance and to impairment of endothelium-dependent flow-mediated vasodilatation, 25) factors which contribute to excessive sensitivity to cold. 26) This vasomotor instability of excessive sensitivity to cold was determined by a 10-question interview, 27) which contained typical complaints of those suffering from unusual coldness.…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25] It is well demonstrated that postmenopausal status is associated with significantly reduced arterial NO activity 24) and thus leads to an increase in local vascular resistance and to impairment of endothelium-dependent flow-mediated vasodilatation, 25) factors which contribute to excessive sensitivity to cold. 26) This vasomotor instability of excessive sensitivity to cold was determined by a 10-question interview, 27) which contained typical complaints of those suffering from unusual coldness.…”
Section: Methodsmentioning
confidence: 99%
“…Young females may have the lower baseline level of skin blood flow to the fingertip in association with higher skin vasoconstrictor activity and/or lower arterial blood pressure. Since the gender difference in fingertip skin temperature becomes more evident in the cold than in a temperate condition [13], this difference may be explained by a sex-related modulation of the thermoregulatory response in skin blood flow during cold exposure as reported previously [14]. To test this hypothesis, we attempted to determine the effect of gender on the contralateral vasoconstrictor response during the ice-water immersion of one hand by comparing the changes in fingertip skin temperature between young males and females.…”
mentioning
confidence: 98%
“…[1][2][3] Autonomic thermoregulation and thermal comfort in response to cold stimuli differ even among healthy individuals, depending on such factors as age, gender, and body composition. [4][5][6][7] Many Japanese women are troubled by a feeling of coldness; in fact, it has been reported that half of all adult women suffer from this problem. 8) Many tend to feel cold, especially at the beginning of winter, but the problem seems to disappear with the arrival of spring.…”
mentioning
confidence: 99%